Auxílio do geoprocessamento para a geração do mapa de suscetibilidade à erosão: o caso do córrego Mandu, Rio Claro/SP - Silva, Alessandra Milano [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The mining of sand, currently, is essential for urban growth, by providing input for the building industry. The consequences of this mining activity to environmental triggers may be severe and irreversible. Among the major impacts caused by sand mining the riparian vegetation removal is detached. The riparian vegetation is essential for balance and maintaining the local ecosystem. For all that had been shown, is possible to verify the importance of environmental studies in areas wich there are mining. This study aimed specially to assess environmental impacts triggered by a mining, located near the headwaters of the stream Mandu, situated in Ajapi, District of Rio Claro-SP. For this purpose, we used remote sensing techniques and GIS to produce thematic maps of slope, pedology, geology, land use and occupation of the soil, and riparian vegetation, using the capabilities of GIS / ArcGIS. The slope map was based on data from the Cartographic IGC 1979, scale 1:10,000. For the production of pedological and geological maps were used Semi-Detailed soil survey of the state of São Paulo, 1981 (1:100,000) and the Geological Map of Zaine (1994), scale 1:50,000, respectively. Since the maps of Use and Land Occupation and Riparian Forest were obtained by visual interpretation of the image of CBERS 2010 following the merger between the HRC and CCD images. From these mappings, and through multi-criteria analysis, map of susceptibility to erosion was made, which supported the environmental assessment of the studied area, indicating susceptible and unsuitable areas for the deployment of economic activities and urban sprawl. This study serves as a model can be replicated in other watersheds, assisting in the proper use planning and land use, aiming at the rational use of natural resources

A mineração de areia, atualmente, é indispensável para o crescimento urbano, por fornecer insumo para a construção civil. As conseqüências que esta atividade mineradora desencadeia ao meio ambiente podem ser graves e irreversíveis. Dentre os principais impactos gerados pela extração de areia se destaca a retirada da mata ciliar. A vegetação ciliar é indispensável para o equilíbrio e manutenção do ecossistema local. Diante do exposto, vê-se a importância de realizar estudos ambientais em áreas que tenham extração mineral. O presente trabalho teve por objetivo fundamental avaliar os impactos ambientais desencadeados por uma atividade mineradora, localizada próxima à nascente do córrego Mandu, situado em Ajapi, Distrito do município de Rio Claro-SP. Para o propósito, foram utilizadas técnicas de Sensoriamento Remoto e SIG, para elaborar os mapas temáticos de declividade, pedológico, geológico, de uso e ocupação do solo, e da mata ciliar, utilizando-se os recursos do SIG/ARCGIS. O mapa de declividade foi elaborado com base nos dados do Plano Cartográfico do IGC de 1979, na escala 1:10.000. Para a produção dos mapas pedológico e geológico foram utilizados o Levantamento Pedológico Semi-Detalhado do Estado de São Paulo de 1981 (1:100.000) e o Mapa Geológico de ZAINE (1994), na escala 1:50.000, respectivamente. Já os mapas de Uso e Ocupação do Solo e da Mata Ciliar foram obtidos por meio da interpretação visual da imagem CBERS de 2010, resultante da fusão entre as imagens HRC e CCD. A partir desses mapeamentos e através da análise multicritério, foi elaborado o mapa de susceptibilidade à erosão, que subsidiou a avaliação ambiental da área de estudo, indicando áreas susceptíveis... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Erosão; Mineração; Impacto ambiental; Mining of sand - Impacts; Ecosystem